Chlorine Dioxide Treatment Modulates Ripening-Related Genes and Antioxidant System to Improve the Storability of Tomato - Me-Hea Park; Siva Kumar Malka (Journal of Food Quality)
Chlorine dioxide (ClO2) is used to maintain quality and safety of fresh produce. However, ClO2 action mechanism in fresh produce is unknown. In this study, firstly, we evaluated the efficacy of ClO2 treatment on the quality, chilling injury, and calyx molding of tomatoes stored at two different temperatures. Then, ClO2 effect on the expression of cell wall- and ripening-related genes and on the activity of antioxidant enzymes was investigated. Tomatoes were treated with gaseous ClO2 for 15 min before transferring them to 13°C for 12 days and/or 4°C for 14 days, followed by 5 days at 20°C (shelf-life conditions). ClO2 treatment marginally reduced the rate of respiration but did not affect ethylene production at 13°C and 4°C storage or at shelf-life conditions. When stored at 13°C, treatment with ClO2 reduced the loss of firmness, with concomitant repression of pectin esterase 1, a cell wall-related gene. Additionally, at 13°C storage conditions, ClO2 treatment maintained tomato quality in terms of soluble solid content, titratable acidity, and color and was associated with the downregulation of the ripening-relatedethylene response factors B3/C1/E1 and the induction of antioxidant genes encoding catalase and ascorbate peroxidase. At 4°C storage conditions, ClO2 at a concentration of 15 ppm not only maintained the firmness and quality of tomatoes but also inhibited pitting during shelf-life with a concomitant increase of catalase activity. Moreover, treatment with 15 ppm ClO2 significantly reduced the calyx molding that is generally observed in fruits stored at 13°C and under shelf-life conditions. Hence, our results indicate that ClO2 treatment effectively maintained tomato quality and inhibited calyx molding by partially regulating ripening-related genes and antioxidant systems, thereby improving the storability of postharvest tomatoes.